تأثير المادة البادئة والمادة المسرعة على الخواص الميكانيكية للبولي استر غير المشبع - عامر الأزكي (Tishreen University, 2017)
يهدف البحث إلى دراسة تأثير مواد الإضافة ( الميثيل إيثيل كيتون بيروكسيد MEKP + الكوبالت نفتنات) على القيم المميزة لمنحنيات الشد ( إجهاد الشد والاستطالة النسبية عند التحطم ) لعينات من البولي استر غير المشبع، المسلحة وغير المسلحة بطبقة من الألياف الزجاجية العشوائية. أظهرت نتائج الاختبارات أن البارامترات المدروسة (إجهاد الشد والإستطالة النسبية عند التحطم) تتأثر بوضوح بمواد الإضافة وأن النسب المثلى للعينات غير المسلحة المحضرة على البارد هي:(1% MEKP + 1% Cobalt Naphthenate) و (0.8% MEKP + 1% Cobalt Naphthenate) وللعينات المسلحة بطبقة من الألياف الزجاجية والمحضرة على البارد هي: (1% MEKP + 0.8% Cobalt Naphthenate) و ((0.2-0.4) % MEKP + 1% Cobalt Naphthenate ). أظهرت الاختبارات أيضاً أن أفضل قيم للشد عند التحطم يمكن الحصول عليها عند تحضير العينات على الساخن بدرجة حرارة 100 Cºوذلك بعد حدوث التصلب في الفرن والمعالجة الحرارية عند هذه الدرجة لمدة زمنية 15 min. This search aims to study the effect of additive materials ( Ethyl Methyl Keton Peroxide MEKP , Cobalt Naphthenate ) at the important values of (stress-strain) curves ( stress and elongation at break ) for the preparing specimens from reinforced and non- reinforced with fiber glass unsaturated polyester resin. The result showed that the investigated parameters are clearly affected with using additive materials and the optimum concentration for non-reinforced specimens which was curing in room temperature was (1% MEKP + 1% Cobalt Naphthenate) and (0.8% MEKP + 1% Cobalt Naphthenate), and for reinforced specimens with fiber glass was:( 1% MEKP + 0.8% Cobalt Naphthenate) and ((0.2-0.4) % MEKP + 1% Cobalt Naphthenate). The results showed also that it is possible to get the better values of tensile stress at break when the specimens was curing in oven at 100 Cº and treated at this temperature for 15 min